Electrifying green synthesis: recent advances in electrochemical annulation reactions. Issue 15 (16th July 2020) - Martins, Guilherme M.; Zimmer, Geórgia C.; Mendes, Samuel R.; Ahmed, Nisar
Abstract : Herein, electrochemical annulations involving mediators and mediator-free conditions have been discussed. Also, the use of sacrificial electrodes has been explored. Abstract : Electricity originating from renewable resources can be used for highly sustainable and economically attractive applications. With electrons as the mass-free reagent, the use of a stoichiometric amount of oxidants in annulation reactions can be avoided, thereby eliminating the production of waste. Considered as a modern reaction configuration, the availability of electrochemical methods is expanding synthetic applications in the field of organic chemistry. Electrochemical transformations possess many benefits over traditional reagent-based methodologies, such as high functional group tolerance, mild conditions, easy scale up setup, high yields and selective transformations. In this review, we targeted electrochemical annulation reactions involving mediators and mediator-free conditions with generation of new C–C, C–heteroatom and heteroatom–heteroatom bonds, their mechanistic insights, as well as the reactivity of substrates. We also explain the recent use of sacrificial electrodes in annulation reactions.